Analysis and Engineering Practice of Factors Affecting Top-Coal Recovery in a Large Dip Coal Seam - Xinglong Huang; Ying Chen; Yang Li; Fengshuo Jia; Shengjian Liang; Xiufeng Zhang; Yang Chen; Qianjia Hui; Zhiwen Wang; Zhaoju Zhang; Zhijie Zhu; Dequan Sun (Advances in Civil Engineering)
The recovery of top coal in the caving face directly impacts the efficiency of mining coal resources. The geological conditions and mining parameters are well known to be significant influences on the recovery of top coal. This study focused on the 9-301 working face, which is located in a thick coal seam with a large dip angle. The influences of the coal seam’s dip angle, mining direction, and coal caving mode and interval on the recovery were analyzed using PFC2D simulation. Field trials were also carried out. The results of the numerical calculations show that the recovery of top coal is clearly affected by the dip angle, with recovery decreasing as the dip angle is increased. Mining from the top to bottom along the dip of the coal seam is beneficial to improve recovery. The top-coal recovery using the multicycle-sequence coal caving method is higher than when using single-sequence coal caving and single-interval coal caving modes. The top-coal recovery using “one cutting and one caving” (coal caving interval of 0.8 m) was higher than that under two cuttings and one caving (coal caving interval of 1.6 m). During the field trials, the recovery of top coal under different caving intervals and modes was measured. The results show that the recovery of top coal is optimal when using one cutting and one caving with multicycle-sequence coal caving modes. The field measurements are consistent with the simulation results. The results of this study can help guide additional research for optimizing the recovery of top coal from thick coal seams with large dip angles.